Ejercicios Isométricos en el desarrollo de la fuerza en adultos mayores - Muñoz Álvarez, Manuel Alfonso (2025)
This research aimed to determine the effectiveness of a training program based only on isometric exercises for developing muscular strength in a group of older people. For this specific case, men and women belonging to the group of senior citizens of the Ecuadorian Institute of Social Security in Riobamba were chosen. The research approach was quantitative, the design was quasi-experimental, and its type was field; the evaluation technique was the grip strength test, and the instrument used for data collection for the pre-and post-test was the hand dynamometer. The population of this group consisted of 90 participants over 65 years of age, of which only those who wished to be part of this project and who also met the requirements to be able to execute it were taken into account; based on this, the sample consisted of 12 people, 11 women representing 92% of the sample and one man with 8%. The training program was created to develop grip strength, and the duration of each level was approximately 4 weeks. The first level strengthened and established muscle memory; the following two levels focused on improving stability. The instrument used for the exercises was a string rope.